The Network behind the Chronicle - Leah Shopkow (Medievalista)
Two chronicles, the Chronicle of Andres and the Chronicle of Evesham, although different from each other in many ways, both contain remarkable first-person singular legal narratives about cases shepherded by their authors through the curia of Innocent III. Although the chronicles share no content, the similarity may be explained by one writer’s influence over the other. The Evesham author, Thomas of Marlborough, had been a student and was an intimate of Stephen Langton; he was also a fellow student of Richard Poore. Andres and Canterbury had long-standing connections, and when William of Andres brought his case to the curia, he was advised by Langton and the monks. Richard Poore heard Andres’s case as a judge-delegate, and was probably responsible for it being returned to the pope for final judgment. The four men came together at the translation of the relics of Thomas Becket in 1220. This network of connections may go a long way to explain how two otherwise unconnected individuals produced such similar legal narratives. In the following period, the professionalization of law precluded the creation of further similar narratives.